Private and Social Returns to Investment in Education : The Case of Turkey with Alternative Methods - Patrinos, Harry Anthony; Psacharopoulos, George; Tansel, Aysit (Taylor and Francis, 2021)
This paper estimates private and social returns to investment in education in Turkey, using the 2017 Household Labour Force Survey (latest available at the time of writing) and alternative methodologies. The analysis uses the 1997 education reform of increasing compulsory education by three years as an instrument. This results in a private rate of return on the order of 16% for higher education and a social return of 10%. Using the number of children younger than age 15 in the household as an exclusion restriction, sample selection correction is applied, and it shows that the returns to education for females are higher than those for males. Contrary to many findings in other countries, private returns to those working in the public sector are higher than those in the private sector, and private returns to those who followed the vocational track in secondary education are higher than those in the general academic track. The paper discusses the policy implications of the findings.